2010
DOI: 10.1016/j.jep.2010.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Dual effects of crude extracts obtained from Petiveria alliacea L. (Phytolaccaceae) on experimental anxiety in mice

Abstract: Preparations using different fresh parts of Petiveria alliacea caused opposite effects on experimental anxiety in mice. However, predicting the extent to which flavonoid content present in Petiveria alliacea extracts differentially induces anxiolysis or anxiogenesis in mice was not possible. Further studies will be necessary to elucidate the effects of flavonoids or other substances present in Petiveria alliacea extracts on experimental anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 14 publications
1
13
0
1
Order By: Relevance
“…The OF test results showed an increase in the total number of crossings and in the number of central quadrants crossed, suggesting anxiolytic activity. Similar result was reported by Blainski et al (2010) who observed the same activity in OF and EPM tests conducted with extracts from different parts of the plant. The presence of metabolites such as polyphenols may have contributed to these results (Ariza et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The OF test results showed an increase in the total number of crossings and in the number of central quadrants crossed, suggesting anxiolytic activity. Similar result was reported by Blainski et al (2010) who observed the same activity in OF and EPM tests conducted with extracts from different parts of the plant. The presence of metabolites such as polyphenols may have contributed to these results (Ariza et al, 2007).…”
Section: Discussionsupporting
confidence: 90%
“…As described by Blainski et al (2010), each animal was orally administered (gavage) with 900 mg/kg of Petiveria alliacea L. hydroalcoholic extract dissolved in saline solution (0.9% NaCl). This oral dose was chosen because the strongest effects of the whole plant extract were observed with this concentration.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Además, análisis fitoquímico revela que su contenido de flavonoides es mayor en las partes aéreas (Blainski et al 2010). …”
Section: Discussionunclassified
“…We reviewed the available literature on diazepam for the three major rodent ARDEB assays: EPM, OF and LD. This review identified 172 articles containing relevant data (Assie et al, 1993;Bahi et al, 2014;Barbosa et al, 2008;Baretta et al, 2012;Barnes et al, 1990;Bellavite et al, 2011;Belzung and Agmo, 1997;Bhatt et al, 2013;Bhattacharya and Mitra, 1991;Birkett et al, 2011;Blainski et al, 2010;Borsini et al, 1993;Brioni et al, 1994;Carneiro et al, 2005;Carro-Juarez et al, 2012;Cechin et al, 2003;Cha et al, 2005;Chen et al, 2004;Choleris et al, 2001;Cole and Rodgers, 1995;Colla et al, 2015;Consoli et al, 2007;Contreras et al, 2011;Costa et al, 2011;Costall et al, 1990;Da Silva et al, 1996;Dalvi and Rodgers, 2001;de A Vieira et al, 2013;de Almeida et al, 2012;de Castro et al, 2007;de Melo et al, 2006;de Sousa et al, 2007;de-Paris et al, 2000;Drapier et al, 2007;R. W. Dunn et al, 1989;1998;Ene et al, 2015;Engin et al, 2009;Ennaceur et al, 2010;Fajemiroye ...…”
Section: Summary Measuresmentioning
confidence: 99%